A Low-Complexity and High-Throughput RTL Design of a BCH (15,7) Decoder - Hendra Setiawan (LPPM ITB, 2012)
The Bose, Chaudhuri and Hocquenghem (BCH) codes form a large class of powerful random-error correcting cyclic codes. However, the implementation of its decoder requires high-complexity computation resources with a huge number of sequential circuits. This paper presents a low-complexity register transfer level (RTL) circuit design of a BCH decoder. In accordance with the table relationship between the syndrome and the error bit position, we propose a circuit that is mostly occupied by combinational elements without any sequential evolvement. Therefore the designed system has a low complexity and high throughput properties. The implementation of the BCH (15,7)decoder on Virtex 5 FX70TFF1136 requires 77 look-up tables (LUTs) with the maximum throughput reaching 1.7 Gbps.